2018
DOI: 10.1088/1748-605x/aa93c0
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release of FGF-2 and BMP-2 in tissue engineered periosteum promotes bone repair in rats

Abstract: The aim of this study was to prepare chitosan-collagen (CS/COL) scaffolds that could release fibroblast growth factor-2 (FGF-2) and bone morphogenetic protein 2 (BMP-2), and to study the effect of this scaffold on bone repair. By improving the double emulsion/solvent evaporation technique, BMP-2 was encapsulated in poly(lactic acid)-poly(ethylene glycol)-poly(lactic acid) (PELA) microcapsules, to the surface of which FGF-2 was attached. The CS/COL scaffold carrying the microcapsules was prepared by freeze-dryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 38 publications
(42 reference statements)
0
18
0
Order By: Relevance
“…In this study have shown that indirect co-culture can promote the synthesis of type and collagen bers by ADSC bFGF , and successfully induce themselves differentiate into broblasts [29][30]. Lee et al [31] added connective tissue growth factor to the culture medium to differentiate bone marrow umbilical cord mesenchymal stem cells into broblasts. Yin et al [32] colonized mesenchymal stem cells on interlaced scaffold materials.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In this study have shown that indirect co-culture can promote the synthesis of type and collagen bers by ADSC bFGF , and successfully induce themselves differentiate into broblasts [29][30]. Lee et al [31] added connective tissue growth factor to the culture medium to differentiate bone marrow umbilical cord mesenchymal stem cells into broblasts. Yin et al [32] colonized mesenchymal stem cells on interlaced scaffold materials.…”
Section: Discussionmentioning
confidence: 77%
“…It is one of the important wound healing factors in the body, has a wide range of biological activities and can affect early in ammation, granulation and the entire wound repair process such as tissue regeneration, epithelialization, and tissue remodeling,thus, has an important application value [13].Our data indicate successfully induced the ADSCs into broblasts by bFGF in vitro, and con rmed that bFGF can signi cantly increase the proliferation of differentiated broblasts, moreover the expression of collagen.However, the growth factor half-life is short and the biological permeability is poor, so it is very easy to be inactivated, and repeated dosing is required to maintain the local concentration [13]. Additionally, studies have shown that bFGF injection is associated with severe anemia, which limits the systemic application of bFGF [14][15]. Therefore, it is necessary to achieve continuous release and an effective concentration of bFGF, in order to provide a suitable microenvironment for the directed differentiation of stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32] A variety of different exogenous chemical or physical stimuli were tested, such as soluble growth/differentiation factors, as well as the application of mechanical forces (i.e., loading). [33][34][35][36][37][38][39][40] Finally, many types of cells have been used alone or in coculture. [41][42][43][44][45][46][47][48] An engineered scaffold-based strategy is the starting point of the recent innovative therapies, for which the choice of material properties, manufacturing methods and component treatments, is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Our work makes high level gene expression of BMP-2 possible and lays the foundation for future applications of BMP-2 in gene therapies for orthopedic conditions including bone defects 12,13 as well as in bone tissue engineering. 14,15 Material and methods…”
Section: Introductionmentioning
confidence: 99%